PENGARUH INOVASI PRODUK DAN PELAYANAN TERHADAP MINAT BELI KONSUMEN JOHN’S BAKERY DI KOTA BATAM - ALAN FABUARI; SYAIFULLAH . (LP2MTBM MAKARIOZ, 2020)
The purpose of this research is to analyze the influence of product innovation and service of buying interest in John's BakeryBatam.The methods used in this study used multiple linear analyses and hypothesis tests. Results of multiple linearregression equations obtained Y value = 9,584 + 0, 515X1 + 0, 319X2 + e. The value of coefficient of determination (R2) is:0.643. From the test results T obtained t value count > T table (4.768 > 1.98) which indicates that product innovationspartially influence positive and significant to the buying interest. As for the service variables get the value of T count > T table(4.701 > 1.98) indicating that the service variables influence positive and significant to the buying interest. From the F testresult obtained the result F count > F table (99.134 > 3.08). From the explanation above, it can be concluded that thevariable product innovation and service influence positive and significant towards buying interest in John's Bakery Batam.